Financial Management Behavior: Pengaruh Financial Technology, Locus of Control, dan Financial Literacy Mahasiswa - Pamungkas, Mayhendra Satria; Prasetyo, Tri Utomo (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2025)
Financial management behavior refers to how a person organizes and manages their financial resources. This study aims to analyze the influence of financial technology, locus of control, and financial literacy on the financial management behavior of Management students in the Special Region of Yogyakarta. Students face many challenges in managing their own finances, such as allocating pocket money for daily needs, tuition fees, and spending on social and entertainment activities. This study attempts to confirm the results of previous studies by using different scopes and data analysis methods. This study involved 126 students majoring in Management in the Special Region of Yogyakarta who used financial technology applications to manage their finances. Sampling was carried out using a non-probability sampling method with a combination of purposive sampling and convenience sampling techniques using an online questionnaire. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) to test the research hypotheses. The results of the study indicate that financial technology, locus of control, and financial literacy partially have a positive and significant effect on financial management behavior, where locus of control is the most dominant variable